PRAKTEK AKUNTANSI RUMAH TANGGA PADA IBU IBU SUKU BALI YANG BERDOMISILI DI JAKARTA - Gusti Ayu Shinta Sukmadevi (2023)
This study aims to find out accounting practices in Balinese mothers' households and to find out how Balinese housewives apply accounting related to planning, recording, and decision making. This study uses qualitative methods. In collecting data using daily observations, observation techniques, interviews and documentation studies. This research was conducted in the Jakarta area. The results of this study are that mothers plan their finances with a monthly period, mothers record their needs as well as record the realization of their financial transactions, such as recording costs for Yadnya, for example Dewa Yadnya, Manusa Yadnya and Bhuta Yadnya. The cost of Dewa Yadnya is like buying offerings for prayers and other big ceremonies that are carried out in Jakarta and the recording is done by the housewife by writing in books and in Media Excel, and making decisions such as investment and storage with all considerations. the need for what has been planned and recorded. Accounting practice and the benefits of applying accounting in household life are useful for knowing the distribution of income and expenses in meeting household needs, making household finances detailed and well-organized, being more open to the head of the family regarding financial activities and preventing the family from debt activity